2000
DOI: 10.1029/2000jd900341
|View full text |Cite
|
Sign up to set email alerts
|

Ice‐supersaturated regions and subvisible cirrus in the northern midlatitude upper troposphere

Abstract: Abstract. Humidity and temperature data from the Measurement of Ozone by Airbus in-service Aircraft (MOZAIC) project have been used to produce maps of probability for ice supersaturation in two 50 hPa thick layers centered around 200 and 250 hPa. As the MOZAIC data cover only international air routes, the resulting maps cover mainly the northern midlatitudes. The data of ice supersaturation have then been correlated with data of frequency of occurrence of subvisible cirrus from the Stratospheric Aerosol and Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
60
0
2

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 29 publications
5
60
0
2
Order By: Relevance
“…ISSRs have similar vertical and horizontal scales and occurrence distribution to SVC (e.g. Gierens et al, 2000;Spichtinger et al, 2003a) and are observed with various ground-, air-, and spaceborne sensors. Statistics in respect to the tropopause location are less frequently reported.…”
Section: Comparison With Ice Supersaturation Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…ISSRs have similar vertical and horizontal scales and occurrence distribution to SVC (e.g. Gierens et al, 2000;Spichtinger et al, 2003a) and are observed with various ground-, air-, and spaceborne sensors. Statistics in respect to the tropopause location are less frequently reported.…”
Section: Comparison With Ice Supersaturation Measurementsmentioning
confidence: 99%
“…The limited vertical resolution (∼ 3 km) of MLS and integration along the line of sight (∼ 200 km) will reduce the detection sensitivity for ISSR by a factor of 0.2 compared to data from the Measurements of OZone and water vapour in Airbus In-service airCraft experiment (MOZAIC). Gierens et al (2000) found that the MOZAIC flights from 1995 to 1997 spent about 15 % of their time in ice supersaturated air masses. Stratospheric ISSR events were only rarely found in the MLS data, but only a crude tropopause determination was applied in the analyses and may create biases in the results (Spichtinger et al, 2003b).…”
Section: Comparison With Ice Supersaturation Measurementsmentioning
confidence: 99%
“…Persistent contrails form at or above ice saturation. Since the frequency of ice supersaturated regions mostly is smaller than 25% in the main flight areas (Gierens et al, 2000), the impact of contrail ice particles on BC from aviation is neglected here.…”
Section: Ei (M)mentioning
confidence: 99%
“…In the tropics, their formation is mainly triggered by deep convection (Jensen et al, 1996) while over the northern middle latitudes, they are associated to the existence of large ice supersaturated regions in the upper troposphere (Gierens et al, 2000). Cirrus cloud formation depends strongly on the existence of small particles that provide the nucleus for ice crystals (Jensen and Toon, 1997).…”
Section: Introductionmentioning
confidence: 99%